Prospective association between 24-hour movement behaviors and mental health among overweight/obese college students: a compositional data analysis approach - Wang, Shuai; Liang, Wei; Song, Huiqi; Su, Ning; Zhou, Lin; Duan, Yanping; Rhodes, Ryan E.; Liu, Huaxuan; Yang, Yi-de; Lau, Wing Chung Patrick; Baker, Julien Steven (Frontiers in Public Health, 2023)
Background: 24-hour movement behaviors, including light physical activity (LPA), moderate-tovigorous physical activity (MVPA), screen-based sedentary behavior (SSB), non-screen-based sedentary behavior (NSB) and sleep are crucial components affecting mental health. This study aimed to examine the associations of movement behaviors with mental health outcomes among overweight/obese college students using a compositional data analysis approach. Methods: Using a prospective design, 437 Chinese college students (20.1±1.7 years; 51.7% female) completed a twowave online data collection, where demographics and movement behaviors (LPA, MVPA, SSB, NSB, sleep) were collected at baseline, while depression, anxiety and stress were measured at the 2month follow-up (Apr-Jul 2022). Compositional data analyses were implemented using R. Results: Depression, anxiety, and stress were negatively associated with time spent in MVPA and sleep (p<0.001) and positively associated with time spent in SSB and NSB (p<0.001). Reallocating 15 min This is a provisional file, not the final typeset article to MVPA from LPA, SSB and NSB predicted improvements in depression (LPA: -0.